Controlling Injection Barriers for Ambipolar 2D Semiconductors via Quasi‐van der Waals Contacts. Issue 11 (19th April 2019) - Wang, Junjun; Wang, Feng; Wang, Zhenxing; Cheng, Ruiqing; Yin, Lei; Wen, Yao; Zhang, Yu; Li, Ningning; Zhan, Xueying; Xiao, Xiangheng; Feng, Liping; He, Jun
Abstract: Barriers that charge carriers experience while injecting into channels play a crucial role on determining the device properties of van der Waals semiconductors (vdWS). Among various strategies to control these barriers, inserting a graphene layer underneath bulk metal may be a promising choice, which is still lacking experimental verification. Here, it is demonstrated that graphene/metal hybrid structures can form quasi‐van der Waals contacts (q‐vdWC) to ambipolar vdWS, combining the advantages of individual metal and graphene contacts together. A new analysis model is adopted to define the barriers and to extract the barrier heights in ambipolar vdWS. The devices with q‐vdWC show significantly reduced Schottky barrier heights and thermionic field emission activation energies, ability of screening the influence from substrate, and Fermi level unpinning effect. Furthermore, phototransistors with these special contacts exhibit enhanced performances. The proposed graphene/metal q‐vdWC may be an effective strategy to approach the Schottky–Mott limit for vdWS. Abstract : Quasi‐van der Waals contacts (q‐vdWC) to ambipolar van der Waals semiconductors (vdWS) combine the advantages of individual metal and graphene contacts together. An analysis model is adopted to extract the barrier heights in ambipolar vdWS. The devices with q‐vdWC show significantly reduced SBH and E a, ability of screening the influence from substrate, Fermi level unpinning effect, and enhanced photoelectrical performances.